Prevalence, characteristics and predicting risk factors of adverse drug reactions among hospitalized older adults: A systematic review and meta-analysis. (August 2021) - Yadesa, Tadele Mekuriya; Kitutu, Freddy Eric; Deyno, Serawit; Ogwang, Patrick Engeu; Tamukong, Robert; Alele, Paul E
Background: Occurrence of adverse drug reactions is a major global health problem mostly affecting older adults. Identifying the magnitude and predictors of adverse drug reactions is crucial to developing strategies to mitigate the burden of adverse drug reactions. This study's objectives were to estimate and compare the prevalences of adverse drug reactions, to characterize them and to identify the predictors among hospitalized older adults. Methods: A comprehensive systematic literature search including both prevalence and risk factors of adverse drug reactions in hospitalized older adults was conducted using PubMed, Scopus and Google Scholar, involving all articles published in English. Descriptive statistics and comparison of means was performed using SPSS version 20.0 and metaprop command was performed in STATA version 13.0. Heterogeneity was assessed using I 2 statistic. Results: A total of 18 studies, involving 80, 695 participants with a median age of 77 years, were included in this study. The pooled prevalence of adverse drug reaction was 22% (95% confidence interval: 17%, 28%; I 2 = 99.23%). Among high-income countries, the prevalence of adverse drug reactions was 29% (95% confidence interval: 16%, 42%) as compared to 19% (95% confidence interval: 14%–25%) in low and middle-income countries ( p value = 0.176). Of the 620 adverse drug reactions categorized, most were type A (89%), which are generally predictable and preventable. Two-thirds (795, 67%) of the adverse drug reactions were probable and most (1194, 69%) were mild or moderate. The majority (60%) of the categorized adverse drug reactions were preventable and less than one-third (31%) were severe. The most consistently reported predictors of adverse drug reactions in hospitalized older patients were medication-related factors, including polypharmacy and potentially inappropriate medications followed by disease-related factors—renal failure, complex comorbidity, heart failure and liver failure. Conclusion: Almost one-quarter of all hospitalized older adults experienced at least one adverse drug reaction during their hospital stay. The majority of the adverse drug reactions were preventable. Medication-related factors were the most consistently reported predictors of adverse drug reactions followed by disease-related factors.